HUBUNGAN PERTEMANAN PADA KOMUNITAS MISKIN PERKOTAAN (Studi Komunikasi Antar Pribadi Pada Komunitas Miskin Di Babakan Hantap, Kecamatan Kiaracondong, Kota Bandung) - ITSNA NURHAYAT EFFENDIE (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2013)
This research aims at finding out an understanding of social relations, i.e.friendships, which are formed and developed by urban society, especially by those who are inpoor social stratum in relation to their survival process. The main research questions arehow meaning and definition of friends are defined by the urban poor community, and howfriendships are formed and implemented in their daily lives.This research employs Herbert Blumer’s symbolic interaction approach that believesthat understanding of a meaning or definition will emerge from communication processesthat are performed by each individual towards other individuals. Techniques used in thisresearch to collect the data are in-depth interview, participant observer and documentationanalysis. This research has been intensively conducted at Babakan Hantap, KecamatanKiaracondong, Kota Bandung.